2020
DOI: 10.1016/j.fertnstert.2019.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the individual effects of metformin and rosiglitazone and their combination in obese women with polycystic ovary syndrome: a randomized controlled trial

Abstract: Objective: To compare the effects of metformin, rosiglitazone, and their combination in obese polycystic ovary syndrome (PCOS) patients with insulin resistance. Design: Prospective randomized controlled trail. Setting: Tertiary teaching hospital. Patient(s): Obese Chinese women (body mass index [BMI] R25 kg/m 2 ) with insulin resistance who fulfilled the Rotterdam criteria of PCOS. Intervention(s): In group 1, 68 patients administered metformin (1,500 mg/day); in group 2, 67 patients administered rosiglitazone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 34 publications
5
73
1
2
Order By: Relevance
“…Fixeddose combination of rosiglitazone/metformin is approved and is available in the U.S., indicated when NIDDM is not well controlled with a single drug. Yujing et al (1) reported no side effects related to rosiglitazone in their study. Metformin was well tolerated or gradually adapted within 1 week to 5 weeks although one patient withdrew due to intolerance.…”
mentioning
confidence: 81%
“…Fixeddose combination of rosiglitazone/metformin is approved and is available in the U.S., indicated when NIDDM is not well controlled with a single drug. Yujing et al (1) reported no side effects related to rosiglitazone in their study. Metformin was well tolerated or gradually adapted within 1 week to 5 weeks although one patient withdrew due to intolerance.…”
mentioning
confidence: 81%
“…Diarrhea, nausea, abdominal discomfort, anorexia are the most common side effect (63). While, vitamin B12 deficiency with the long term use of metformin (64).…”
Section: Side Effectmentioning
confidence: 99%
“…The waist-to-hip ratio (WHR) was calculated as the waist circumference divided by the hip circumference. Androgen-related symptoms of hirsutism and acne were evaluated as previously reported [22]. Antral follicle count (AFC) were assessed by performing transvaginal ultrasound examination on days 2-3 of menstruation or progestin-induced withdrawal bleeding.…”
Section: Clinical Samplesmentioning
confidence: 99%
“…Plasma glucose, estradiol (E 2 ), progesterone, total testosterone (TT), luteinizing hormone (LH), folliclestimulation hormone (FSH), sex hormone binding globulin (SHBG), and fasting insulin (FINS) levels were measured as reported previously [22]. The free androgen index (FAI) was calculated as TT (nmol/L)/SHBG (nmol/L) × 100.…”
Section: Clinical Samplesmentioning
confidence: 99%
See 1 more Smart Citation